Psychosis in Parkinson's disease in a Southeast Asian cohort: prevalence and clinical correlates - Vanessa Wai Ling Mok; Lai Gwen Chan; Justine Chay Boon Goh; Louis Chew Seng Tan (Singapore Medical Journal)
Introduction: Psychosis is a prominent neuropsychiatric symptom of Parkinson's disease (PD) and is associated with negative outcomes, such as poorer quality of life and greater rate of functional impairment. Early identification of patients with PD at risk of developing psychosis facilitates appropriate management to improve outcomes. However, this phenomenon has not been examined locally. This study aimed to examine the prevalence of PD-associated psychosis in the local setting, identify any associated risk factors, as well as characterise the cognitive trajectory of patients with PD with psychosis. Methods: A retrospective cohort of 336 patients with PD, who presented to the National Neuroscience Institute, Singapore, in 2006 and 2007 and attended follow-up visits through to 2013 was analysed. The data analysed included scores from clinician assessments of cognitive function, disease severity and presence of psychotic symptoms, conducted when clinically appropriate during patients’ medical visits. Survival analysis and logistic and linear regression analysis were performed. Results: Psychosis was diagnosed in 63 patients with PD, indicating a prevalence of 18.8% for PD-associated psychosis. Incidence of psychosis in PD was calculated to be 40 per 1,000 person-years. No significant association was found between demographic variables and the odds of developing psychosis in PD. Regression analyses found that the presence of psychosis significantly predicted greater cognitive decline and disease severity. Conclusion: Psychosis has a significant presence among the PD population in Singapore, possibly serving as an indicator of more rapid cognitive decline and progression of PD severity.